2021
DOI: 10.1186/s12935-021-02052-1
|View full text |Cite
|
Sign up to set email alerts
|

GNRH1 and LTB4R might be novel immune-related prognostic biomarkers in clear cell renal cell carcinoma (ccRCC)

Abstract: Background Clear cell renal cell carcinoma (ccRCC) occupied most of renal cell carcinoma (RCC), which associated with poor prognosis. The purpose of this study is to screen novel and prognostic biomarkers for patients with ccRCC. Methods and results Firstly, Gene Expression Omnibus database was used to collect microarray data for weighted gene co-expression network construction. Gene modules related to prognosis which interest us most were picked o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…CSNK1E positively regulated the expression of differentially expressed immune genes related to survival such as AGER, GNRH1, SHC1, IRF9, TNFRSF25, LMBR1L, LTB4R, and LTB4R2. A recent study reported that AGER, GNRH1, SHC1, IRF9, and LTB4R could be used as prognostic factors of KIRC [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…CSNK1E positively regulated the expression of differentially expressed immune genes related to survival such as AGER, GNRH1, SHC1, IRF9, TNFRSF25, LMBR1L, LTB4R, and LTB4R2. A recent study reported that AGER, GNRH1, SHC1, IRF9, and LTB4R could be used as prognostic factors of KIRC [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that immune checkpoint blockade (ICB) therapy and combination regimens significantly improve survival in ccRCC patients [ 30 , 31 ]. Therefore, based on our previous studies [ 12 ], we further investigated LTB4R’s biological functions and mechanisms in the development of renal clear cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of leukotriene B4 receptor 1 (LTB4R) with LTB4 to activate leukocytes and prolong their survival as IAGs is significant in acute inflammatory responses [ 11 , 12 , 13 ]. BLT1 (LTB4R) is also an attractive drug target for allergic airway inflammation, inflammatory arthritis, atherosclerosis, and psoriasis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microslaw et al [ 17 ] demonstrated that the expression levels of chorionic gonadotropin beta subunit and GnRH1 in the blood of cancer patients might be valuable in indicating tumor metastasis and spread. Wu et al [ 18 ] demonstrated that GnRH1 and LTB4R are prognostic biomarkers for patients with ccRCC.…”
Section: Discussionmentioning
confidence: 99%